Analisis Pendapatan, Tingkat Inflasi Dan Harga Emas Dalam Penyaluran Kredit Rahn Pada PT Pegadaian Indonesia Tahun 2013-2022 - Ajeng Windi Astuti; Anjel Ezania Sihombing; Monalisa Lumbantobing; Nur Aini Simbolon; Ros Juliana Lubis; Syarifah Syarifah; Tri Kurnia (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Sharia Pawn (Ar-Rahn) is an agreement between a lender and a party who lends money. A lien is a right to tangible goods that is given to a debtor who wants to get ahead of the debtor, and the item is taken after the person has the money to redeem the lien. Rahn is a pawn service product based on sharia principles, where customers are only charged with administrative fees, additional mortgage and maintenance costs. The purpose of this study was to determine the evolution of income, inflation rates and gold prices in Rahn's credit distribution at PT. Pawn shops in Indonesia. The data analysis method used is descriptive analysis with a quantitative approach used as a data analysis method. The data source comes from secondary data Literature research and documentation are used as data collection techniques. The subject to be studied is PT. Pegadaiic Indonesia 2013- 2022. The results show that gold income and prices are directly proportional to rahn credit distributed to the community. Meanwhile, inflation is not directly proportional to the rahn credit distributed to the public.